Antimalarial Potential of Fraction 5 from Ethanolic Leaves Extract of Artocarpus Altilis - Einstenia Kemalahayati; Hilkatul Ilmi; Agriana Rosmalina Hidayati; Marsih Wijayanti; Lidya Tumewu; Suciati; Achmad Fuad Hafid; Aty Widyawaruyanti (Universitas Airlangga, 2023)
Background: Artocarpus altilis leaf extract (AAL.E) was separated by VLC, and six fractions were obtained. Fraction 5 (AAL.E.5) showed antimalarial activity with an IC50 value of 3.71 µg/mL. Objective: This study aimed to determine the antimalarial activity of AAL.E.5 subfractions against P. falciparum, the mechanism of action against Plasmodium Falciparum Malate quinone oxidoreductase (PfMQO), and the active substances. Methods: The AAL.E.5 was separated by open-column chromatography and eluted with chloroform-methanol gradient elution in order of increasing polarity. The antimalarial activity of all subfractions was assessed using a lactate dehydrogenase (LDH) assay against P. falciparum and the mechanism of action of the PfMQO enzyme. The profiles of the most active subfractions were analyzed using High-Performance Liquid Chromatography (HPLC). Results: The separation of fraction 5 (AAL.E.5) yielded 11 subfractions (AAL.E.5.1–AAL.E.5.11). Screening antimalarial activity at 10 Î¼g/mL in this subfraction showed that only five subfractions (AAL.E.5.6-AAL. E.5.10) inhibited P. falciparum and two subfractions (AAL.E.5.6 and AAL.E.5.10) inhibited the PfMQO enzyme. Only subfraction 6 (AAL.E.5.6) inhibited both, with IC50 values of 6.609 µg/mL and 20.34 µg/mL. The thin layer chromatography profile of AAL.E.5.6 revealed reddish-orange spots, indicating the presence of flavonoid compounds, and was also presumed from the UV-visible to HPLC chromatogram for band I in the 300 – 400 nm range and band II in the 240–285 nm range. Conclusion: Subfraction 6 has antimalarial activity against P. falciparum and is thought to have a mechanism of action in PfMQO. Based on the TLC, HPLC, and UV-Vis spectra, subfraction 6 was assumed to be a flavonoid.